Desenvolvimento, validade e confiabilidade da escala observacional de marcha para crianças com paralisia cerebral espástica - Priscila Albuquerque de Araujo (2007)
In clinical practice, the observational gait assessment is often used to evaluate gait disorders. However, the instruments available in the literature do not present satisfactory validity and reliability. This study reports the content validity, criterion validity and reliability of a new observational gait scale aimed to describe the gait pattern of children with spastic cerebral palsy. Four experienced physical therapists evaluated, in two separated sessions, the gait of eighteen children with spastic cerebral palsy (11 boys and 07 girls, average age 9 years). Kinematic data have been collected of the ankle/foot complex, knee, hip and pelvis with the instrumented gait analysis. In order to evaluate criterion validity and intra and inter-rater reliability, the observational data had been compared with the instrumented gait analysis data, the two sessions and the raters. Weighted kappa test was used to assess the agreement between data. The scale presented substantial validity for knee and moderate validity for the ankle/foot complex. Intra-rater reliability was substantial for the ankle/foot complex, knee and hip and moderate for pelvis. Inter-rater reliability was substantial for the ankle/foot complex and knee, and moderate for the hip. This observational gait scale demonstrated satisfactory reliability and validity for the ankle/foot and knee. New strategies must be created to improve the hip and pelvis reliability.